Feasibility of an endoscope-dominated side-to-end hypoglossal-facial anastomosis: an anatomical study - Yang, Xiaobing; Man, Dulegeqi; Yang, Yang; Li, Xingang (Frontiers in Surgery, 2023)
Surgical simulation of endoscope-dominated side-to-end hypoglossal-facial anastomosis was performed to evaluate the feasibility. Eight anatomical cadaver heads (16 sides) were recruited. Steps in conventional procedures were abbreviated or omitted. A facial nerve was first harvested near its external genu and used for side-to-end hypoglossal-facial anastomosis. The stump of the used facial nerve was truncated and recycled immediately caudal to the facial recess in another anastomosis and then recycled again at the stylomastoid foramen. As a recycled stump becomes too short to ensure side-to-end anastomosis, the hypoglossal nerve was transected in situ, and endoscopic end-to-end hypoglossal-facial anastomosis was attempted. Surgical simulation and quantitative measurement methods were used to analyze the anastomosis effects of different harvested sites of facial nerve. Several steps in the conventional procedures provide little benefit in endoscopic surgery. A facial nerve stump recycled at the stylomastoid foramen is too short to ensure a tensionless side-to-end anastomosis. Endoscopic end-to-end hypoglossal-facial anastomosis was feasible, although it required more time than classical microsurgical anastomosis. The greater agility of an endoscope enables conventional surgical steps to be overlapped or interweaved into the procedure.The multiple surgical fields and ability to manipulate the viewpoint provided by an endoscope have brought about breakthroughs in classical surgical paradigms. In addition, it is best to choose the sites of facial nerve harvested near the external genu. If unavailable, an alternative section site could be selected immediately caudal to the facial recess,but cannot be distal to stylomastoid foramen. The length of the stump should be individualized and preferably optimized with a nerve simulator.